Use of potentially antagonistic fungi to control some Hevea pathogens in vitro - Jayasuriya K E (Papers presented at IRRDB seminar 5-8 November 1996 Sri Lanka p22)
Fungi potentially antagonistic against Hevea pathogens were isolated from different sources and their antagonistic mechanisms against individual pathogens were studied. Basidiomycetes fungi viz. Tramates spp and some Coprophillus group fungi caused hyphal inhibition of R. lignosus by hyphal interference mechanism, similar to the control mechanism of Phlebiopsis gigantea (Peniophora gigantea), the commercial biocontrol agent of Heterobasidion anosum of pine. Trichoderma and Gliocladium spp antagonised most of the Hevea pathogens in paired cultures by antibiosis.
Keywords: Antagonistic fungi; Hevea-Pathogens; Sri Lanka